The Antiacne Activity of Sunkist Peels Methanol Extract in Propionibacterium Acne-Induced Acne Vulgaris - Mutia, Maya Sari; Damayanti, Etha Wilda Hasiani; Suyono, Tan; Sihotang, Widya Yanti (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2023)
Treatment with acne vulgaris is a challenge because the complex pathophysiology of acne vulgaris. One of the natural products that potentially use as a herbal medicine is Sunkist peel. The peel of Sunkist is more inclined to end up as waste from domestic industries. The aim of this study was to investigate the antiacne activity of the Sunkist peel methanol extract gel in vivo study. The experimental study used by applied Sunkist peel extract gel to rats injected intradermally with Propionibacterium acne suspension. One hour before the injection of Propionibacterium acnes suspension, all rats were applied to a topical gel based on the group. Control, standard, Sunkist Peel Extract Gel-I, II, and III groups received gel base, clindamycin, 5%, 10%, and 15% of Sunkist peel extract gel, respectively. This study indicates the methanol extract of Sunkist orange peel with a yield of 8.73% revealed the presence of some phytochemicals, including alkaloids, flavonoids, tannins, and saponins. Sunkist orange peel methanol extract gel significantly reduced the size of acne vulgaris lesions after 7-14 days of extract application (p-value <0.05). It is in line with the histological study that the gel concentration increased, followed by the growth of the epidermal layer. This study sstrongly indicates that Sunkist orange peel methanol extract has an antiacne effect in a physically stable gel form.